Beginning of forever - Bybee, Catherine (Bybee, Catherine. D'Angelos series, 2023)
"Tasting wine is not enough: sommelier Giovanni D'Angelo wants to create it. To put his family first, he's always deferred his dreams-a vineyard to run, a woman to marry. But a three-week vineyard tour in Italy could set him back on track. For Emma Rutledge, wine is in her blood. Intent to run the family wine business one day, she finds that the men in her family are only intent to push her out of it. But that's fine-she's got a plan. When Gio and Emma meet on a wine tour in Tuscany, their shared aspirations fuel an undeniable chemistry. Returning home to California, they work toward setting up Emma's vineyard and a label of their own. But when Emma receives a life-altering diagnosis, she worries it's all been for nothing. As Emma works to cement her family legacy while dealing with this unexpected challenge, Gio tries to convince her that their future isn't just wine. It's each other"--